Impact of on-chip interconnect frequency-dependent R(f)L(f) on digital and RF design. - Yu Cao (IEEE Transactions on VLSI systems)
On-chip global interconnect exhibits clear frequency dependence in both resistance (R) and inductance ( L). In this paper, its impact on modern digital and radio frequency (RF) circuit design is examined. First, a physical and compact ladder circuit model is developed to capture this behavior, which only employs frequency independent R and L elements, and thus, supports transient analysis. Using this new model we demonstrate that the use of dc values for R and L is sufficient for timing analysis (i.e., 50% delay and slew rate) in digital designs. However, RL frequency dependence is critical for the analysis of signal integrity, shield line insertion, power supply stability, and RF inductor performance.